Exploring the Value Chains in the Small Ruminant Sector: A brief review of the literature - Awad, Rula; Brahmi, Aziza Mohamed; Titi, Hosam; Jaouad, Mohamed; Boubaker, Aziza Gasmi (Journal of agricultural, environmental and veterinary sciences, 2024)
The current study was conducted in order to deepen the understanding of how small ruminants fit into the economy and enhance the competitiveness of live animals and value-added products. This study focuses on previous efforts to understand what value chains mean in the small ruminant sector, what it really means to deliver value to customers, understand the links between production, marketing, etc. activities of products and services in an effective manner, and the role of value added in providing wealth to all stakeholders who participated. Previous literature was reviewed in detail especially for that included a case study and detailed analysis of the five value chain elements, identification of actors and promoters, horizontal and vertical links, flow mapping through the chain, identification of marketing channels, key challenges and opportunities and review the possible interventions within vertical and horizontal interactions and management structure according to this literature. It was found that strategies for good breeding, improving health care, providing credit, improving markets, improving pasture productivity and rehabilitating them, in addition to the involvement of potential actors and the coordinated efforts of all stakeholders; It will increase the productivity of small ruminants and improve product/market development and thus have sustainable value chains for small ruminants.
Keywords: Value Chain; Value Chain Analysis; Small Ruminants; Challenges; Review